A review on algae-mediated adsorption and catalytic processes for organic water pollution remediation - Suresh, R.; Rajendran, Saravanan; Chen, Wei-Hsin; Soto-Moscoso, Matias; Sundaram, Thanigaivel; Jalil, Aishah Abdul; Rajamani Sekar, Suresh Kumar (Frontiers in Materials, 2024)
Wastewaters consist of organic pollutants that have environmental concerns. Wastewaters are treated by different methods, but efficient, low-cost, and sustainable techniques still need to be developed. Algae-based water pollution remediation techniques are considered to be sustainable approaches. This review exclusively discusses the facets of macro and microalgae in the treatment of organic toxicants. The current trends of algae-mediated water treatments have been discussed under adsorption and degradation methods. A focus on algae fuel cell, algae mediated activation of oxidizing agents, Fenton-like reactions, and photocatalysis was given. The need of algae-based adsorptive and catalytic materials was mentioned. The role of algae in the synthesis of catalysts which were employed in pollutant removal methods was also explained. The integrated algaemediated water treatment techniques were also highlighted. The toxicant removal performances of different algae-based materials in the water medium were summarized. The conclusion and future prospects derived from the literature survey were described. This review will be helpful for researchers who are working in the field of sustainable water pollution remediation.